2016
DOI: 10.3390/ma9070526
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Zinc-Tin-Sulfur Thin Film Using Spin-Coating Technology

Abstract: Cu 2 ZnSnS 4 (CZTS) thin films were deposited on glass substrates by using spin-coating and an annealing process, which can improve the crystallinity and morphology of the thin films. The grain size, optical gap, and atomic contents of copper (Cu), zinc (Zn), tin (Sn), and sulfur (S) in a CZTS thin film absorber relate to the concentrations of aqueous precursor solutions containing copper chloride (CuCl 2 ), zinc chloride (ZnCl 2 ), tin chloride (SnCl 2 ), and thiourea (SC(NH 2 ) 2 ), whereas the electrical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…The CZTS thin film shows the (112), (220) and (312) planes corresponding to 2θ values of about 28.437°, 47.302° and 56.094° respectively. This result is almost congruent with the previous studies [17][18][19][20][21]. This ensures that the polycrystalline tetragonal structure, that is CZTS, is formed.…”
Section: Structural Propertysupporting
confidence: 92%
See 1 more Smart Citation
“…The CZTS thin film shows the (112), (220) and (312) planes corresponding to 2θ values of about 28.437°, 47.302° and 56.094° respectively. This result is almost congruent with the previous studies [17][18][19][20][21]. This ensures that the polycrystalline tetragonal structure, that is CZTS, is formed.…”
Section: Structural Propertysupporting
confidence: 92%
“…In 2016 Yeh et al [19] demonstrated the deposition of CZTS thin films by spin coating method. They showed the variation of optical band gap of CZTS with Cu/(Zn+Sn) ratio where the band gap ranges from about 1.7 eV to about 1.4 eV and also obtained the cell conversion efficiency of 1.13%.…”
Section: Introduction mentioning
confidence: 99%
“…For electrically high quality CZTS absorber films, it is necessary to increase the formation of Zn Sn acceptors and to diminish the Sn Zn donors. This might be possible when the Zn/Sn ratio is higher than 1 [31].…”
Section: Czts Absorber Layer Characterizationsmentioning
confidence: 99%
“…Up to 21% and 21.7% efficiency have been achieved for second generation CdTe and CIGS solar cell [6]. But due to the toxicity of cadmium and selenium, and less availability of tellurium and indium, an alternative material CZTS has achieved great attraction among the researchers during last couple of years [7,8].…”
Section: Introductionmentioning
confidence: 99%